Molecular mechanisms and applications of natural transformation in bacteria - Niu, Changcheng; Wu, Hao; Wang, Xiaona; Hu, Liying; Han, Yanping; Qiao, Jianjun (Frontiers in Microbiology, 2025)
Natural transformation is a process in which bacteria uptake exogenous DNA from the environment during a transient physiological state called competence. The DNA can either autonomously replicate or integrate into the bacterial chromosome through homologous recombination. Natural transformation has been studied for nearly a century. Recently, the rapid development of synthetic biology has led to the widespread use of natural transformation as a gene-editing tool for modifying industrial strains. A better understanding of the basic principles of natural transformation can enhance its biotechnological applications. This article provides a detailed overview of the natural transformation process, from initiation to completion. It focuses on the molecular mechanisms involved in natural transformation in both Gram-positive and Gram-negative bacteria. The article also analyzes factors that influence the activation of natural transformation, detailing the regulatory processes and signaling pathways involved. It further explores the potential biological functions of natural transformation. Finally, it discusses various applications of natural transformation in gene editing, offering insights into its potential for modifying industrial strains.